Application of Expert Systems in Library and Information Work - Entsua-Mensah, Clement (Ghana Library Journal, 1996)
A new development in the field of Artificial Intelligence, a branch of computer science, enables computers to exhibit signs of intelligent behaviour to simulate problem-solving process of human beings. The method, known as Expert System, has had diverse applications in a number of fields and disciplines. The paper explores possible introduction of expert systems in library and information work. To help better appreciation, background information on the various connotations of the concept, and what constitutes expert systems is provided. It is observed that expert systems are gradually finding applications in cataloguing, reference service and information retrieval aspects of information work and some of these applications are reviewed.